Approaches towards menstrual cycle disorder therapy in reproductive-aged women with long COVID - V.V. Kaminskyi; A.V. Serbeniuk; Y.O. Kumpanenko (Publishing House TRILIST, 2023)
Background. The mirror of a female's reproductive health is the menstrual cycle. The SARS-CoV-2 pandemic itself acts as a significant stressor. This leads to women's overall health and life quality disturbance. Moreover, patients struggle with long COVID effects, which is a prolongation of symptoms after recovery. Due to the expression of angiotensin-converting enzyme type 2 receptors in the intestinal mucosa and inflammation, the gastrointestinal (GI) tract is also triggered by the virus. Objectives. To assess the efficacy of the chosen treatment approach in women with changes in premenstrual syndrome and cyclicity due to long COVID with or without GI symptoms. Material and methods. A single-centre longitudinal interventional study was organized. Were studied data from the conducted tests (progesterone level, ultrasound follicle scan, etc.) and surveys. Then the effectiveness of the suggested treatment with the use of oral and vaginal forms of progesterone was evaluated. The study was held in the Kyiv City Center of Reproductive and Perinatal Medicine (Ukraine) from January to June 2021. Results. On average 78% patients without GI symptoms experienced relief after 3 months and 89% patients after 6 months of suggested treatment. 71% patients with GI symptoms experienced improvement after 3 and 87% of them after 6 months. The vaginal progesterone had better results compared to oral form. Averagely 6-8% experienced side effects (nausea, hypotension, less compliance) due to progesterone intake. The vaginal micronised progesterone also presented better results than oral with fewer side effects compared to the total number of participants. Conclusions. The proposed approach has shown particular correction of the menstrual cycle disturbances in women with long COVID. Vaginal micronized progesterone offers more promising outcomes in patients with GI symptoms and disrupted absorption, compared to the oral form. Further investigation is required for a more reasonable conclusion.